A case of HIV at Woodworks ltd (b) : a slew of curve balls - Sharda, Kirti (London : Indian Institute of Management, Ahmedabad, 2020)
This case provides us with more information on Basu's deteriorating performance. Jai used to evaluate Basu's performance monthly. Basu was expected to ensure that he achieved this productivity daily. Jai was very flexible and lenient with him. However, there was an incident after which Jai asked Basu to quit immediately. He offered him one month's salary as compensation. At that time, Basu was in a very senior position in Woodworks Ltd. and Jai did not have anyone who could take up Basu's responsibilities.
Description based on XML content.
Keywords: elektronické knihy; electronic books; HIV-positive persons -- Employment; Personnel management; Social responsibility of business; HIV infections -- Economic aspects